Evaluation of Liver Enzymes and calculation of AST to ALT ratio in patients with acute viral hepatitis - Pandeya , Arun; Shreevastva , Naveen Kumar; Dhungana , Arun; Pandeya , Anup (Europasian Journal of Medical Sciences, 2021)
Background: Acute viral hepatitis is a common liver-associated abnormality encountered in clinical practice. The number of biochemical parameters is estimated to detect a hepatic abnormality, which can measure the severity and types of damage to hepatocytes, among which liver enzymes and bilirubin levels are assessed routinely which are raised in acute viral hepatitis. Objective: This study aims to assess the liver enzymes, such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), bilirubin, and calculation of AST to ALT ratio in acute viral hepatitis and to compare these parameters with the control group. Methodology: This study included a total of 81 subjects diagnosed with acute viral hepatitis as cases and age and sex-matched, the same number of healthy subjects as control. Serum levels of AST and ALT, alkaline phosphatase (ALP), and bilirubin were analyzed using standard methods. Serum AST to ALT ratio was calculated. Data analysis was done using SPSS Version 17.0 and the results were expressed as mean ±standard deviation (SD). Results: A mean serum activities of aminotransferases were statistically significantly raised in viral hepatitis compared to that in control.AST (514.85±350.66 VS 25.65±5.29; p<0.001) and ALT (781.65±525.69 VS 27.94±6.50; p<0.001). Similarly, serum levels of(ALP)were significantly increased in acute viral hepatitis compared to that in control (202.17±75.46 VS 98.83±27.99; p<0.001. However, a ratio of AST to ALT was decreased significantly (0.66±0.15 VS 0.94±0.21; p= 0.001) in acute viral hepatitis compared to that in control. Conclusion: Both the aminotransferases and bilirubin levels are raised significantly, where, a rise in ALT is greater than a rise in AST, hence, the ratio of AST to ALT is decreased significantly in acute viral hepatitis than that in control. Thus, this decreased pattern of AST to ALT can diagnose acute viral hepatitis at an early stage and can help appropriate care and treatment to the patients. DOI: https://doi.org/10.46405/ejms.v3i2.255